Cooperation, quorum sensing, and evolution of virulence in Staphylococcus aureus - Pollitt, Eric J.G.; West, Stuart A.; Crusz, Shanika A.; Burton-Chellew, Maxwell N.; Diggle, Stephen P. (ASM Press, 2014)
The virulence and fitness in vivo of the major human pathogen Staphylococcus aureus are associated with a cell-to-cell signaling mechanism known as quorum sensing (QS). QS coordinates the production of virulence factors via the production and sensing of autoinducing peptide (AIP) signal molecules by the agr locus. Here we show, in a wax moth larva virulence model, that (i) QS in S. aureus is a cooperative social trait that provides a benefit to the local population of cells, (ii) agr mutants, which do not pro- duce or respond to QS signal, are able to exploit the benefits provided by the QS of others (“cheat”), allowing them to increase in frequency when in mixed populations with cooperators, (iii) these social interactions between cells determine virulence, with the host mortality rate being negatively correlated to the percentage of agr mutants (“cheats”) in a population, and (iv) a higher within-host relatedness (lower strain diversity) selects for QS and hence higher virulence. Our results provide an explanation for why agr mutants show reduced virulence in animal models but can be isolated from infections of humans. More generally, by providing the first evidence that QS is a cooperative social behavior in a Gram-positive bacterium, our results suggest conver- gent, and potentially widespread, evolution for signaling to coordinate cooperation in bacteria.